Adaptación de lentes de contacto en paciente de sexo masculino de 23 años de edad, con astigmatismo hipermetropico - Mina Jonson, Tamara Veatriz (2024)
Astigmatism and hyperopia are two of the most common refractive errors. We normally say that a patient has a refractive problem when, due to poor optical functioning, the eye is not able to provide a good image since it does not focus correctly. in the retina. This clinical case is about a 23-year-old male patient who does not wear glasses and goes to an optometric consultation for the first time and indicates that he has presented the following symptoms; blurred vision, headache, eye fatigue, rubbing and squinting. The respective assessment was carried out by applying optometric tests such as ocular motility, visual acuity without correction and with correction both subjectively and objectively. Thus determining that our patient has a case of hyperopic astigmatism. And therefore optometric treatment is prescribed according to the patient's needs. This treatment consists of the adaptation of contact lenses. The patient is then told that they must attend an optometric consultation every month to evaluate the progress, so that the respective follow-up is given so that the optical treatment is successful. During the first month with the respective optical prescription, the patient obtained improvements in his vision, symptoms such as headache and eye fatigue, the need to squint and other symptoms were eliminated.